The Dynamics of 2024 Election Crimes in North Maluku - Hasan, Aslan; Rada, Arisa Murni (Faculty of Law, Universitas Lampung, 2024)
This research examines the characteristics of election crimes at each stage of the electoral process in North Maluku and analyzes the handling patterns employed by Sentra Gakkumdu, focusing on data that has been largely overlooked in previous research. Using an empirical legal research method with a conceptual and statutory approach, the research provides a comprehensive assessment of election crime enforcement. The findings reveal that the highest number of reported violations occurred during the plenary recapitulation stage (42 cases), followed by the voting and vote-counting stage (33 cases), the campaign stage (32 cases), and the nomination stage (2 cases). Despite the high number of reports, Sentra Gakkumdu faced significant challenges in case handling. Of the 109 reported cases, only 7 reached a court decision, while the majority were halted at the discussion, investigation, or administrative correction stages. These findings highlight the low success rate in prosecuting election crimes and underscore the need for improved coordination and enforcement mechanisms within Sentra Gakkumdu. This research contributes to the development of election law and provides valuable insights for strengthening the effectiveness of election crime enforcement.